2000
DOI: 10.1002/1531-8249(200012)48:6<885::aid-ana9>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological effects of interferon β‐1a in relapsing multiple sclerosis

Abstract: Cognitive dysfunction is common in multiple sclerosis (MS), yet few studies have examined effects of treatment on neuropsychological (NP) performance. To evaluate the effects of interferon beta-1a (IFNbeta-1a, 30 microg administered intramuscularly once weekly [Avonex]) on cognitive function, a Comprehensive NP Battery was administered at baseline and week 104 to relapsing MS patients in the phase III study, 166 of whom completed both assessments. A Brief NP Battery was also administered at 6-month intervals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Treatment type may contribute to impairment of cognitive functions in people with MS. We found that attention, memory, language, and informationprocessing speed were significantly better in patients receiving immunomodulatory drugs compared to those on immunosuppressive medications. This agreed with Fischer and colleagues, who reported that interferon Beta 1a had a significant favorable effect on attention, memory, visuospatial abilities, information processing, and problem solving [22]. Available immune-modulatory treatments for multiple sclerosis rapidly inhibit the inflammation and reduce the progression of brain atrophy, and they may also have neuro-protective properties [6].…”
Section: Discussionsupporting
confidence: 84%
“…Treatment type may contribute to impairment of cognitive functions in people with MS. We found that attention, memory, language, and informationprocessing speed were significantly better in patients receiving immunomodulatory drugs compared to those on immunosuppressive medications. This agreed with Fischer and colleagues, who reported that interferon Beta 1a had a significant favorable effect on attention, memory, visuospatial abilities, information processing, and problem solving [22]. Available immune-modulatory treatments for multiple sclerosis rapidly inhibit the inflammation and reduce the progression of brain atrophy, and they may also have neuro-protective properties [6].…”
Section: Discussionsupporting
confidence: 84%
“…Use of disease modifying therapy for multiple sclerosis has a demonstrable slowing effect on dysfunction 60. Rudick et al 61 demonstrated that patients with relapsing-remitting disease on interferon β-1a therapy had a significant reduction in the progression of brain atrophy during the second year of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Two‐year data from the phase III study showed that IFN β ‐1a (Avonex ® , Biogen, Inc.) was effective in slowing disability progression, reducing exacerbations, reducing disease activity as measured by magnetic resonance imaging (MRI) scans, and improving cognitive function (4, 16–19). The annual exacerbation rate calculated after 2 years of IFN β ‐1a treatment in the present study of 96 patients (mean = 0.52) is slightly lower than that observed in 85 patients from the phase III study after 2 years of IFN β ‐1a treatment (mean = 0.67) (4).…”
Section: Discussionmentioning
confidence: 99%